Development of VR Learning Media in Vocational Schools as a Form of Technology Integration - Hastutiningsih, Arum Dwi; Eko, Nuryadin; Elviana, Elviana; Pramudiyanto, Pramudiyanto (Jurnal Pendidikan Vokasi Raflesia, 2024)
Research and Development (R&D) Borg Gall approach to develop VR learning media that aligns with the curriculum and the needs of vocational school students. Through R&D stages such as needs analysis, design, development, and evaluation, VR content is designed to provide deep and relevant learning experiences related to the workplace. Adequate technological infrastructure is also considered to support VR implementation in the vocational school learning environment. Furthermore, teacher training is conducted to ensure effective VR utilization in the learning process. Continuous evaluation is carried out to measure the effectiveness and feasibility of VR learning media usage in vocational school. This research aims to provide practical guidelines for the development and implementation of VR-based learning media in vocational school, focusing on student engagement and improving learning quality.